Impacto do controle de tensão e potência reativa (Volt-var) em sistemas de distribuição com alta penetração de geração distribuída fotovoltaica - Martins, Renata Mota (2023)
There has been a growth in the development of distributed energy resources in recent years. The additional penetration of these resources is causing problems of overvoltage at the connection point, for the reverse active power flow. Other problems such as increased technical losses, thermal overload of the conductors and increased taps of voltage regulators are being reported in the literature. Mitigation proposals for the overvoltage problem involving control by the own inverters of distributed generation are being widely discussed. However, the use of these types of control is not completely consolidated. Issues involving the location, configuration of the control functions, fairness in the participation of each distributed generation unit in the voltage regulation ancillary service, impacts on energy losses and elements of the distribution system still need to be evaluated and defined. Thus, we seek to analyze the effects of Volt-var control by intelligent inverters on the power quality of medium and low voltage systems. Two test systems were studied, the IEEE 33 bus system, and a low voltage secondary system. For the simulations in the IEEE 33 bus system, three load situations were considered: system with loads with inductive, unitary and capacitive power factor, all with voltage control in two simultaneous buses, where different slopes of the Volt-var curve were analyzed in both the inverters. For this system, the effects on the connection point voltage, energy losses, substation power factor, and the participation of each inverter in voltage control were analyzed. For the low voltage system, loads with inductive power factor were considered, and with photovoltaic distributed generation at all points in the system. The Volt-var control was employed in all inverters and different operating modes of the Volt-var control were analyzed, and compared with the traditional solution of reconducting the circuit. For this system, the impacts on voltages, losses, currents and the participation of each inverter in the control were analyzed. All simulations were done in OPENDSS and Python in Quasi-static time series mode for 24 hours. According to the results obtained, with the Volt-var control it was possible to mitigate the problems of undervoltage and overvoltage in medium and low voltage systems. Volt-var control can be beneficial for the power factor in the substation. However, it can result in increased technical losses, and increased currents in conductors. It was verified that there is no fair participation of the inverters for the voltage control.